PEMANFAATAN GAMIFIKASI UNTUK MENINGKATKAN OLAH-RASA MURID PADA PEMBELAJARAN AGAMA KATOLIK DI SMP ST. IGNASIUS MEDAN - Siringo, Riana; simbolon, Erikson (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Catholic Religious Education instruction focuses not only on knowledge acquisition but also on the development of students' affective sensibilities (sensory processing). However, teacher-centered instruction has resulted in suboptimal student engagement in internalizing Christian values. This study aims to describe the state of students' affective sensibilities and analyze the use of gamification to enhance these sensibilities within Catholic Religious Education classes at St. Ignasius Junior High School, Medan. A qualitative, descriptive approach was employed. Data were collected through observation, interviews, and documentation, then analyzed using an interactive analysis model, with validity verified through source and technique triangulation. The findings indicate that students' affective sensibilities develop through emotional engagement, empathy, faith reflection, the internalization of Christian values, self-awareness, and moral responsibility. The use of gamification fosters a more active, enjoyable, and collaborative learning environment, thereby boosting motivation, participation, and the internalization of Christian values. Thus, gamification serves as an effective instructional strategy for developing students' affective sensibilities in Catholic Religious Education.